Specifying Metadiscoursal Signals in the Novel Pride and Prejudice and its Two Persian Translations By Copple’s model (1980) - Boroujeni, Esmaiel Kaboli (Richtmann Publishing, 2012)
Finding out the metadiscoursal signals in any language and analyzing their usage specially in meaning transferbetween two different languages is very important. The present paper adopted the model presented by Vande Copple (1980), tofind all of the metadiscoursal signals in the first five chapters of the novel Pride and Prejudice by Jane Austen. The number ofmetadiscoursal signals in all of the related parts in the original novel was compared with those of its two Persian renderings byPooranfar and Ardakani by a comparative study using Vande Copple’s model. The results of the study showed that the numberof metadiscoursal signals usage in the TL translation made by Ardakani was more than of those in Pooranfar’s translation.However, considering both translations, they were poor in transferring the original metadiscoursal signals into the Persianlanguage and it resulted to the less comprehensibility of them comparing to that of original novel. Besides, the consistency,meaningfulness and communicativeness of the translated texts were in a lower level than the original due to the lower number ofmetadiscoursal signals. As a result, it was made clear that the use of metadiscoursal signals is necessary and complementary inany kind of discourse use.